Continuous quadratus lumborum type II block in partial nephrectomy - Graça,Rita (2018)
Abstract Background and objectives: Quadratus lumborum block was first described in 2007 and currently there are descriptions of its achievement through four different injection points. This blockage provides abdominal wall and visceral analgesia, and one of its mechanisms is the dispersion of the local anesthetic into the paravertebral space. We describe the performance of a continuous quadratus lumborum type II block for postoperative analgesia in a partial nephrectomy. Case report: A 64-year-old woman, scheduled for partial left laparoscopic nephrectomy. During the procedure, due to technical difficulties, an incision was made in the left flank to facilitate the surgical approach. In the early postoperative period, a continuous quadratus lumborum type II block was performed using ultrasonography as part of the multimodal analgesic strategy. Initially, 20 ml of 0.2% ropivacaine was administered and 3 cm of catheter were introduced into the interfascial space. Subsequently, a continuous infusion of 5.2 mL.h−1 of 0.2% ropivacaine was given for 48 hours. In the first 24 postoperative hours, the patient reported no pain at rest or on movement. In the following 24 h, she was free of pain at rest and only a slight pain (2/10) on movement. Conclusions: Continuous quadratus lumborum type II block was an effective postoperative analgesic option. Blocking of somatic nerves and visceral afferent pathways provided abdominal and visceral wall analgesia, allowing the reduction of opioid consumption. We consider relevant to explore the analgesic capacity of the quadratus lumborum block and its different approaches, as well as the possibility of it becoming an alternative in patients scheduled for kidney surgery.